2020
DOI: 10.2174/1573413715666190709120019
|View full text |Cite
|
Sign up to set email alerts
|

2D Honeycomb Silicon: A Review on Theoretical Advances for Silicene Field-Effect Transistors

Abstract: : Catalysed by the success of mechanical exfoliated free-standing graphene, two dimensional (2D) semiconductor materials are successively an active area of research. Silicene is a monolayer of silicon (Si) atoms with a low-buckled honeycomb lattice possessing a Dirac cone and massless fermions in the band structure. Another advantage of silicene is its compatibility with the Silicon wafer fabrication technology. To effectively apply this 2D material in the semiconductor industry, it is important to carry out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…In recent years, several reviews and monographs on Si‐based 2D materials have been published 8,26,27,62–67 . However, Ge‐based 2D materials have rarely been reviewed despite the important findings and extensive theoretical and experimental research on the output of these unique materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several reviews and monographs on Si‐based 2D materials have been published 8,26,27,62–67 . However, Ge‐based 2D materials have rarely been reviewed despite the important findings and extensive theoretical and experimental research on the output of these unique materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is worth exploring whether the application scope of 2D Ge will be wider than that of 2D Si. In recent years, several reviews and monographs on Si-based 2D materials have been published. 8,26,27,[62][63][64][65][66][67] However, Ge-based 2D materials have rarely been reviewed despite the important findings and extensive theoretical and experimental research on the output of these unique materials. To bridge this gap, here, we present a methodically structured review on the latest progress in predictive modeling, fabrication, and fundamental physical property modulation of Ge-based 2D materials, viz., germanene and its derivatives, Ge-IVA binary compounds, Ge-VA binary compounds, and Ge-VIA binary compounds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the computational models of silicene-based transistors [ 16 , 17 ], rigorous efforts were invested by many groups of researchers. The absence of bandgap in pristine silicene did not halt its exploration for nanotransistor applications.…”
Section: Introductionmentioning
confidence: 99%
“…The development of two-dimensional (2D) materials has been motivated by the success of monolayer honeycomb carbon (C)-graphene [11]. While the discovery of graphene has more than 15 years of history, the honeycomb Si-based monolayer-silicene has only attracted research interest in the recent years as shown by the trend of publication numbers [12,13] despite its potential compatibility with the present Si-dominant fabrication processes. In 2015, Tao et al [14] demonstrated the first silicene-based transistor using synthesis-transfer fabrication technique.…”
Section: Introductionmentioning
confidence: 99%